2014
DOI: 10.1186/1743-422x-11-65
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of small ruminant lentivirus A4 subtype isolates and assessment of their pathogenic potential in naturally infected goats

Abstract: BackgroundSmall ruminant lentiviruses escaping efficient serological detection are still circulating in Swiss goats in spite of a long eradication campaign that essentially eliminated clinical cases of caprine arthritis encephalitis in the country. This strongly suggests that the circulating viruses are avirulent for goats.To test this hypothesis, we isolated circulating viruses from naturally infected animals and tested the in vitro and in vivo characteristics of these field isolates.MethodsViruses were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…The genotype E1 was also present in the mammary gland or in associated tissues; this may ensure the SRLV transmission to offspring since the main transmission route in goats is lactogenic (Blacklaws et al, 2004;Gjerset et al, 2009). The data obtained from the mammary gland supported the results obtained by Deubelbeiss et al (2014), in which the low pathogenic virus genotype A4 was abundantly represented in the mammary gland. In contrast to the genotype A4, the increased genotype E1 proviral load was not involved in the development of histopathological lesions, thus confirming genotype E1 as a highly attenuated SRLV.…”
Section: Discussionsupporting
confidence: 76%
“…The genotype E1 was also present in the mammary gland or in associated tissues; this may ensure the SRLV transmission to offspring since the main transmission route in goats is lactogenic (Blacklaws et al, 2004;Gjerset et al, 2009). The data obtained from the mammary gland supported the results obtained by Deubelbeiss et al (2014), in which the low pathogenic virus genotype A4 was abundantly represented in the mammary gland. In contrast to the genotype A4, the increased genotype E1 proviral load was not involved in the development of histopathological lesions, thus confirming genotype E1 as a highly attenuated SRLV.…”
Section: Discussionsupporting
confidence: 76%
“…Infection with new subtypes may possibly lead to virus adaptation to a new host and promote changes of its biological and pathogenic properties [ 6 ]. It was shown that viruses representing the A4 subtype were generally attenuated in naturally infected goats, however, they caused histopathological changes in the mammary tissue [ 26 ]. It was remarkable that the A17 subtype was present in 7 out of 23 goats from flock 6, which could suggest broad dissemination of this subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, genotype and subtype surveys of the circulating SRLVs should be encouraged. Many studies describe phylogenetic analysis of SRLVs found during epidemiological surveys or in outbreaks of diseases, but only a few of them describe the histopathological lesions observed in target organs [ 16 , 17 , 18 ]. For example, mild mammary lesions with a multifocal method to diffuse mononuclear inflammatory interstitial infiltrates have been observed in sheep with arthritis and infected by B2 SRLV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, mild mammary lesions with a multifocal method to diffuse mononuclear inflammatory interstitial infiltrates have been observed in sheep with arthritis and infected by B2 SRLV [ 17 ]. Different histopathological scores have been reported in mammary glands but not in lungs, synovial membranes of joints, or the chorioid plexus of five goats infected by A4 SRLV [ 16 ]. A 13–14 nucleotide deletion in the R region of the LTR has been observed in sheep with a decreased pathology in the lung but not in the udder even though SRLV subgenotypes were not known [ 18 ].…”
Section: Introductionmentioning
confidence: 99%